Abundance and Diversity of Insect Visitors to Ground Cover Plants in Organic Orchard With Bee Hives (Apis Mellifera) in Batu, Indonesia - Budi Purwantiningsih; Amin Setyo Leksono; Bagyo Yanuwiyadi; Zulfaidah Penata Gama (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis)
This study aims to determine the differences in abundance, richness, diversity, evenness, and dominance of insects on ground cover plants and to visually analyse their visiting patterns in organic orchard with bee hives and without bee hives (Apis mellifera) in Batu City, Indonesia. Total visiting insects was 733 individuals from 21 plant species. The most visited plants was Synedrella nodiflora visited by pests, predators pollinators, and detrivors, this shows a picture of close interaction between the two in forming a food web. The abundance and diversity of pollinating insects in orchard with bee hives (62.50) was higher than the abundance and diversity of insects in orchard without bee hives (52.11). Diversity of predatory insects (0.25) in orchard with bee hives was lower than that without bee hives (1.68). The abundance, species richness, and evenness of pests in orchard with bee hives were lower than those without bee hives. The results of independent sample t-test analysis showed that there was no difference in insect composition between the two orchard. Organic orchard with bee hives can reduce the abundance, species richness, and evenness of pests, because bees and other pollinators also act as predators. In both orchard, Episyrpus baltaetus actively visited plant flowers at 08.00 to 14.00 which has the potential as a predators and pollinators.